Differentiated Levels of Teacher Qualifications and the Structure of the Professional Teacher Standards - Zabrodin Yu.M; Gayazova L.A; Sergomanov P.A (Moscow State University of Psychology and Education, 2016)
This article discusses and analyzes the questions effect of professional standards for the preparation and development of professional resources, world experience in the development and implementation of professional standards, typical problems and necessary conditions for increasing the efficiency of the development and implementation of professional standards. The formation of labor functions of teaching staff requirements, taking into account the differentiated c skill levels are formulated in the study. Formulated requirements extend requirements for the qualification of workers which are determined with the Russian Ministry of Labor-specific professional activity types. The study proposed options for the construction of the structure of job functions of the professional teacher standard that correspond differentiated levels of staff qualifications.